Pengaruh Komitmen Profesional, Moral Reasoning dan Budaya Organisasi Terhadap Keputusan Etis Auditor Independen - Gede Mandirta Tama; Ida Ayu Gede Danika Esa Pradnyani; Made Konny Koswara (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to empirically prove: (1) the effect of professional commitment on the ethical decisions of independent auditors, (2) the effect of moral reasoning on the ethical decisions of independent auditors and (3) organizational culture on the ethical decisions of independent auditors. The population of this study is independent auditors in the capital market at KAP in East Java and West Java regions registered with the OJK. The sampling method using total sampling technique obtained a sample of 59 people. Data comes from primary data in the form of respondents' answers to questionnaire statements. The data analysis technique used is the partial least square (PLS) model. The results of this study indicate that professional commitment, moral reasoning and organizational culture have a positive effect on ethical decisions at KAP in the East Java and West Java regions registered with the OJK.